Spectral models of klystrons and travelling-wave tubes - Gritsunov, A. V. (My University, 2010)
An attempt is made to expand the spectral approach, implemented only for the M-type devices yet, onto O-type devices such as one-beam klystrons and travelling-wave tubes. The general features of the new spectral models are described. The used algorithms of simulation are quoted.
Keywords: spectral approach; O-type device; numerical simulation